Understanding the North American Free Trade Agreement (SELA CaracasVE, 1993)
Examines the NAFTA provisions affecting border measures, such as restrictions on exports and imports. Looks at the NAFTA provisions on agriculture, textiles and apparel, energy and the automotive sector. Deals with the treatment of issues such as services, intellectual property rights, investment, the environemnt, and labour. Notes those provisions of the NAFTA that affect the operations of the parties' own governments. Surveys the institutional provisions of the NAFTA.
Additional copy located in the Office of the Secretary-General